Veterinary forensic medicine and forensic sciences - Byrd, Jason H.; Norris, Patricia; Bradley-Siemens, Nancy (Boca Raton, FL : CRC Press, 2020)
While there are several recent books on this emerging field, Veterinary Forensic Medicine and Forensic Sciences sets the bar, covering all relevant aspects in a succinct, easy-to-read, comprehensive format designed to be taught in a single-semester course. Intended to be the premier textbook on veterinary forensic sciences, the book covers the application of veterinary forensic medicine to cases, including the medical perspective as well as law enforcement response, crime scene management, and evidence recovery issues. Coverage includes the scientific and legal principles for veterinary forensic evidence. This clearly delineates it from veterinary-only practices, since the forensic aspects present additional challenges that include evidence recovery and preservation, report writing, and maintaining an evidentiary chain of custody, all the way through expert witness testimony. Some emerging topics that are covered include DNA and genetic evidence, entomological evidence in support of veterinary forensics, animal fighting, situational deaths, including poisonings, domestic violence, and cruelty, sharp and blunt force trauma, gunshot and wound ballistics, sexual assault, nonhuman odontology and osteology, and more. Features Details a process for forensic science case management for humane law enforcement agencies Presents multiple chapters on specific types of trauma analysis in animals Provides developments on current trends in forensic entomology as applied to wildlife crime and minimum postmortem interval determinations Explores national and international considerations in combating organized animal fighting Offers DNA applications for wildlife crime and environmental monitoring Outlines current animal and environmental forensic toxicology legal casework This text offers a straightforward presentation of current practices and includes several real-world case examples throughout to illustrate concepts. Fully illustrated with more than 280 full-color images, Veterinary Forensic Medicine and Forensic Sciences provides the latest in advances and up-to-date field techniques, applicable for student instruction in the classroom and beyond.
Chapter 1. Animal Crime Scene Investigation -- Chapter 2. Humane Law Enforcement: From Initial Report to Final Appeal -- Chapter 3. Animal Genetic Evidence and DNA Analysis -- Chapter 4. Forensic Entomology -- Chapter 5. Animal Bitemarks: Evidence and Application -- Chapter 6. Animal Sexual Assault -- Chapter 7. Blunt Force Trauma -- Chapter 8. Sharp Force Trauma. -- Chapter 9. Gunshot Wounds and Wound Ballistics -- Chapter 10. Non-Human Forensic Osteology. -- Chapter 11. Environmental and Situational Deaths (Chemical, Thermal, Drownings) -- Chapter 12. The Forensic Application of Animal Behavior Analysis -- Chapter 13. Animal Fighting -- Chapter 14. Animal Poisonings -- Chapter 15. Domestic Violence and Animal Abuse.
OCLC-licensed vendor bibliographic record.
Keywords: Veterinary forensic medicine; LAW / Forensic Science; MEDICAL / Veterinary Medicine / Food Animal